Gambling behaviour and motivation in an urban sample of older adult gamblers - Clarke D; Clarkson J (NEW ZEALAND PSYCHOL SOC)
Due to low rates of gambling participation among older adults (65+ years), little is known about gender differences in their gambling behaviour and reasons for gambling. Also, little is known about differences in their motives for different forms of gambling. Following motivational theory, the present study compared the behaviour and motivation of 41 male and 63 female gamblers in Hamilton, New Zealand where a casino was recently opened. Ages ranged from 66 to 87 years. Gambing for rewards was the strongest motivation for both sexes, followed by boredom. There were no significant gender differences, nor interactions between gender and skill/chance preferences on motivation. Regular continuous gamblers had stronger preferences for horse/dog races, scratch tickets or non-casino gaming machines, and had a higher expenditure rate than regular non-continuous gamblers who more strongly preferred Lotto. They also had significantly higher scores on curiosity, stimulation, escape and apathy. Longitudinal and observational studies were suggested to examine the impact of new casinos in towns with large numbers of older adults, and to monitor potential symptoms of problem gambling.
Keywords: SOCIAL ACTIVITY; HEALTH; COMMUNITY; GENDER; 1701 Psychology; 1702 Cognitive Sciences